2009
DOI: 10.1007/s00262-009-0760-1
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral DNA electroporation induces anti-tumor immunity and tumor regression

Abstract: In situ expression of a foreign antigen and an immune-modulating cytokine by intratumoral DNA electroporation was tested as a cancer therapy regimen. Transgene expression in the tumors sustained for 2–3 wks after intratumoral electroporation with mammalian expression plasmid containing firefly luciferase cDNA. Electroporation with cDNA encoding tetanus toxin fragment C (TetC) induced tetanus toxin-binding antibody, demonstrating immune recognition of the transgene product. Intratumoral electroporation with Tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The antitumor effectiveness of intratumoral IL-12 electrogene therapy was demonstrated also in other types of cancer, such as colon carcinoma, renal cancer, lymphoma, breast carcinoma and sarcoma mouse tumor models [75][76][77][78][79][80]. Treatment of CT26 colon carcinoma tumors with 3 times repeated intratumoral IL-12 electrogene therapy resulted in significant inhibition of tumor growth.…”
Section: Preclinical Studies With Il-12 Electro-gene Therapymentioning
confidence: 88%
See 1 more Smart Citation
“…The antitumor effectiveness of intratumoral IL-12 electrogene therapy was demonstrated also in other types of cancer, such as colon carcinoma, renal cancer, lymphoma, breast carcinoma and sarcoma mouse tumor models [75][76][77][78][79][80]. Treatment of CT26 colon carcinoma tumors with 3 times repeated intratumoral IL-12 electrogene therapy resulted in significant inhibition of tumor growth.…”
Section: Preclinical Studies With Il-12 Electro-gene Therapymentioning
confidence: 88%
“…These results are in contradiction with other published reports on IL-12 electrogene therapy. The reason for this discrepancy was not addressed by the authors and remains to be elucidated [80]. Recently, intratumoral IL-12 electrogene therapy combined with small interference RNA (siRNA) targeting microphthalmia-associated transcription factor (Mitf) was evaluated in B16 melanoma [99].…”
Section: Il-12 Electrogene Therapy In Combination With Other Therapiesmentioning
confidence: 99%
“…These effects have been described in melanomas 7–11 , lung carcinomas 12, 13 , fibrosarcomas 14 , pancreatic carcinomas 15 , mammary tumors 16 and colorectal carcinomas 17, 18 . In two studies, antitumor effects were observed after intratumor electrotransfer of an oligonucleotide containing a CpG motif, although each oligonucleotide primarily functioned as an antisense molecule 19, 20 .…”
Section: Introductionmentioning
confidence: 91%
“…We have tested several strategies to trigger tumor immunity in situ . Intratumoral electroporation of D2F2 mammary tumors with cDNA encoding Tetanus toxoid fragment C and IL-12 induced antibody response to Tetanus toxin, T-cell response to endogenous TAA, heavy inflammatory infiltration, partial regression of established tumors and immune memory which protected mice from repeated tumor challenge [80]. These effects are most evident when Tregs are depleted using CD25 mAb, demonstrating a pre-existing, though suppressed immunity to TAA.…”
Section: In Situ Vaccination By Non-surgical Ablationmentioning
confidence: 99%